Casos y cosas: semanario popular (Vol. 1, No. 25) - Imprenta La Region (My University, 1920)
SPANISH: Incluye: El colmo de la cobardía, Cuanta infamia!... un gran negociado, Escalando en el Mercado, La familia Peluda heredó, Quisicosas, La liga Tronchista - Badani

ENGLISH: The height of cowardice, how much infamy!... a big business, climbing in the market, the Hairy family inherited, quisicosas, the Tronchista league - Badani
Cases and things: popular weekly (Vol. 1, No. 25)
Keywords: Periodicals; Satire, Peruvian; Humor; Iquitos (Perú)--revistas; Perú--revistas satíricas